Local conversion of redox inactive molecules into redox active ones: A formaldehyde based strategy for the electrochemical detection of illicit drugs containing primary and secondary amines. (20th January 2021) - Schram, Jonas; Shanmugam, Saranya Thiruvottriyur; Sleegers, Nick; Florea, Anca; Samyn, Nele; van Nuijs, Alexander L.N.; De Wael, Karolien
Highlights: Formaldehyde to allow the electrochemical detection of illicit drugs containing primary and secondary amines. LC-MS/MS confirmation of derivatization mechanism. Novel strategy for the enrichment of electrochemical fingerprints. Successful detection of amphetamine in confiscated street samples. Abstract: Electrochemical techniques have evidenced to be highly suitable for the development of portable, rapid and accurate screening methods for the detection of illicit drugs in seized samples. However, the redox inactivity of primary amines, one of the most common functional groups of illicit drugs, masks voltammetric detection in aqueous environment at carbon electrodes and, therefore, leads to false negative results if only these primary amines are present in the structures. This work explores the feasibility of a derivatisation approach that introduces formaldehyde in the measuring conditions in order to achieve methylation, via an Eschweiler-Clarke mechanism, of illicit drugs containing primary and secondary amines, using amphetamine (AMP) and methamphetamine (MET) as model molecules. As a result the electrochemical fingerprint is enriched and thereby the detectability enhanced. A combination of liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOFMS) and square-wave voltammetric (SWV) measurements is employed to identify reaction products and link them to the observed redox peaks. Although an alkaline environment (pH 12.0) proved to increase the reaction yield, a richer electrochemical fingerprint (EF) is obtained in neutral conditions (pH 7.0). Similarly, the addition of formate improved the reaction conversion but reduced the EF by eliminating a redox peak that is attributed to side products formed in the absence of formate. To illustrate the applicability, the derivatisation strategy is applied to several prominent illicit drugs containing primary and secondary amines to demonstrate its EF enriching capabilities. Finally, real street samples from forensic seizures are analysed. Overall, this strategy unlocks the detectability of the hitherto undetectable AMP and other drugs only containing primary amines, while strongly facilitating the identification of MET and analogues. These findings are not limited to illicit drugs, the insights can ultimately be applied to other target molecules containing similar functional groups. Graphical abstract: Image, graphical abstract